The practices of nurses about palliative sedation on palliative care wards: A qualitative study - Heino Linda; Stolt Minna; Haavisto Elina (WILEY, 2025)
Aim
To describe the practices of nurses concerning palliative sedation in palliative care wards in hospitals.
Design
Qualitative descriptive design.
Methods
A total of 27 nurses were interviewed in six focus groups and one pair interview; the nurses worked on four palliative care wards in three Finnish hospitals and the interviews took place between May and November 2019. The data were analysed using inductive content analysis. The COREQ checklist was used as a guide for reporting this study.
Findings
Three main categories describing nurses' practices concerning palliative sedation were identified: participation in palliative sedation decision-making, sedation implementation and monitoring and information sharing and compassionate care for the patient and relatives.
Conclusions
Nurses play a key role throughout palliative sedation on palliative care wards in hospitals. To develop the quality of care, it is recommended to specify the role of nurses in palliative sedation, increase cooperation between nurses and physicians, and enhance palliative sedation education for nurses.